The platonic experience in nineteenth century : England - Cruzalegui Sotelo, Patricia (1997)
THE PLATONIC EXPERJENCE in Nineteenth-century England explores two areas of interest that have always been of immense importance in my intellectual and emocional life: the philosophy of Plato and British culture and particularly that of the eighteen-hundreds. Plato's presence during the English nineteenth century was especially constant and multiform. lt appeared integrated into poetry in Romanticism, for there was a strong belief throughout most of the nineteenth century that Platonism was a form of poetic literature. In the Victorian age, the period of maximum splendour of interest in Plato, a wide range of interpretations arose both within and outside the academic world. Hence the second part of the century saw the learned research and Utilitarian criticism of George Grote as well as the three editions of the great translation of Plato into English by BenjaminJowett, renowned as a liberal theologian and the moralising Master of Balliol College Oxford. There followed Walter Pater with his aesthete's version of Platonism as a sensual, eroticised and languid philosophy. This thesis is the result of my research on the interpretations, translations and the eminent readings of Plato in the British nineteenth century and it lays clown the following objectives. Firstly, to point out and document the established existence of a Platonic tradition in nineteenth century philosophy and literature which co-existed with the more authentic, to use a commonplace, Aristotelian and empiricist approximation of reality. The second goal is to demonstrate that Platonism was utilised by and adapted to the different images of the world that were forged as the century went by. Examples of these were Utilitarianism, social Darwinism, eugenics, the democracy of the elite, Christian liberalism and Aestheticism. The third objective is to analyse how the prestige of Plato oscillated during different periods of the nineteenth century as well as the way in which this prestige was used with varying degrees of success in arder to valida te ideologies and innovative or alternative ways of life as opposed to those of convention. F ourthly, I wish to highlight the crucial role played by BenjaminJ owett in divulging a Platonism tailored to the Victorian ideals of arder and progress, and also to indicate how this very same Plato furnished and shaped, albeit involuntarily, the banned ideal of the homoerotic relationship of the end-of-the-century aesthetes. My final aim is to suggest the contemporary derivations of sorne of these interpretations, in the field of literature, politics, sexuality and philosophy.